Blockchain dan Teknologi Informasi: Pembawa Perubahan Mahasiswa di Kota Medan - Tarihoran, Anita; Yolanda, Yola; Tarigan, Purnaya Sari (Prodi Akuntansi FEBM Universitas Maritim Raja Ali Haji, 2024)
This study aims to analyse the effect of blockchain and information technology on student change in Medan City. The population in this study was 363 students in the Accounting Study Programme at Mikroskil University. The sampling method used the Slovin formula and obtained 78 students who became research samples. The data testing method used is a quantitative method using a structural equation model with the SmartPLS 3.2.9 programme. The results showed that blockchain has no influence on student change in Medan City, while information technology is able to influence student change in Medan City.